Prevalence and Associated Factors of Overweight and Obesity among Adolescents students: A Cross-Sectional Study in a Developing country - Kadim, Maha A; Abdulrasol, Zainab Abdulameer; Obaid, Ali Fadhil; Abbas, Yasmin Ali; Latif, Noor Amar (South Asian Journal of Social Sciences and Humanities, 2023)
Abstract:Background: The epidemic of obesity in developed countries is commonly associated with poor dietary habits and a sedentary lifestyle. Obesity and overweight are defined as an excessive buildup of body fat and pose a risk to health. Adolescent obesity continues to be a subject of increasing global public health importance and is considered a vital risk factor for obesity and associated morbidity in adulthood. The objective is to determine the prevalence of obesity among school adolescents and estimate the relationship between obesity and some predicted risk factors (physical activity, eating habits). Methods:  A descriptive cross-sectional study was carried out among (500) students in AL-Hilla city from the period 12th January to 2nd April 2022 at (10) secondary schools.  The questionnaire is composed of two parts; Part one: involved the socio-demographic characteristics of students and their parents. This section also includes BMI was calculated by measuring height& weight; weight was measured with domestic scales and height with a meter rule and classified according to international classification. Part two is related to the risk factors of obesity. Data were collected through direct interviews with students for filling the tool required by spending approximately 20-30 minutes. Finally analyzed electronically by using (SPSS) version 24 by application of frequencies, percentages as descriptive, inferential as correlational statistics, and logistic regression. Results: Obesity and overweight were predominant at age (16-17) (58.6 %), and most of them were male (56.4 %) whose come from governmental schools (86.8 %).  28.8% of the sample were overweight and (14.4%) were obese children. Boys are riskier to be overweight and obese than girls ( OR= 1.55, 95%CI (1.33 -1.807). Adolescents who did vigorous physical activity were less risky to be obese one time compared to those with non-vigorous activity OR=1.072, 95% CI= (0.966-1.189). In addition, obesity has a likelihood to decrease five times in a student who consumed the fruit more than three times compared to those with one time (OR= 5.189, 95% CI= 5.189-5.189). Conclusion: The study conclude that around forty-three percent of adolescent school students were either overweight or obese. So, indicated that obesity was predominant at age (16-17) among Iraqi adolescent students aged 14-19 years. In addition, adolescents' eating habits and physical activity were highly significant factors in overweight/ obesity. Therefore, interventions are recommended to focus on these risk variables of overweight and obesity.
Keywords: Obesity; Overweight; Physical activity; Eating habits; Adolescent School student